Rapport der commissie, belast met het onderzoek naar de klachten betreffende het schijvenschuren - Van Zutphen, Jan; Voet, Isidore; de Miranda, S.R. ([Amsterdam]: [s.n.], 1917)
"J.A. Van Zutphen, S.R. De Miranda, I. Voet, H. Rogge, G. Frankfort"